Lao People’s Democratic Republic Poverty Assessment 2020 : Catching Up and Falling Behind - World Bank (World Bank, Washington, DC, 2020)
Lao People’s Democratic Republic (PDR) has made substantial progress in poverty reduction, despite the fact that its resource-based development pattern has historically limited the impact of growth on poverty reduction. Although poverty declined, mirroring economic growth, the impact of growth on poverty reduction was low. As a result, the country lacks productive industries to absorb labor and create high-quality jobs. The Lao Statistics Bureau (LSB) has conducted the LECS at five-year intervals since 1992-1993.The LECS survey is the primary source of official poverty statistics in Lao PDR, providing critical information for monitoring progress on poverty reduction, identifying poor and vulnerable groups, and ultimately informing government policies aimed at poverty eradication. This poverty assessment will provide insights into the success (or lack thereof) of poverty reduction in Lao PDR during the past six years. The report will also help identify poor and vulnerable populations as well as emerging issues that have slowed progress toward inclusive development. The report is divided into two parts. Section 1 provides updates on poverty and inequality in Lao PDR. Section 2 approaches key drivers of poverty and escape routes from poverty by topic.